Uma nova metalo-endopeptidase purificada do cérebro humano que hidrolisa neuropeptideos - Ruchon, Maria Andrea Frota (1994)
A rather limited number of peptidases seem lo be involved in the post-secretory inactivation of peptide hormone messengers. The importance of these proteolytic mechanisms in regulaling hormonal action can be demonstrated by the fact that their effects can be prolonged "in vivo" or "in vitro" by selective inhibitors of these enzymes. In this study, a new endopeptidase was purified from normal human brain. This peptidase exhibits a thermolysin-like character and hydrolyzes bonds on the amino terminus of hydrophobic amino acids, performing a selective cleavage at the Xaa-Phe, Xaa-Leu , or Xaa-Ile doublets ( Xaa = Ser, Phe, Tyr, His, or Gly ) of a number of peptide hormones, including substance P, bradykinin, atrial natriuretic factor (ANF) and angiotensin II. This peptidase also cleaves the 0-(l-4O) amyloid peptide. This enzyme exhibited optimal activity at pH 7,3 - 7,8 and has an apparent molecular weight of 200 KDa. The endopeptidase activity was inhibiled by divalent cation chelators like o-phenanthroline, EDTA and DTT and was insensitive to classical inhibitors of neulral endopeptidase (NEP), angiotensin convertase, and serine and cysteine peptidase, as well as ca rboxy peptidases.